Clusters and innovation: the relationship between membership in clusters organisations and technological maturity of companies in Poland - Mackiewicz, Marta; Pavelkova, Drahomira (Technological and Economic Development of Economy, 2022)
This article aims to investigate the relationship between cluster organisation membership and the performance of companies in terms of their technological maturity. The article introduces and operationalises a new concept of technological maturity which reflects competitiveness, innovativeness, and market reputation of a company in a particular sector. To compare the technological maturity between cluster organisation members and non-members a composite index was created. The study is based on theoretical and empirical analyses. The empirical part is based on firm-level data collected in the survey from 464 companies identified in the technological fields covered by the National Smart Specializations in Poland. A set of statistical tests has been employed to assess whether (a) the indicators differ significantly between cluster organisation members and non-members (b) the composite index differs significantly between cluster organisation members and non-members. Results of the analysis show a positive relationship between being a member of the cluster organisation and the technological maturity of the company. The regression analysis proved that the relationship remains significant when controlling for the industry, geographical location, and size of a company. The article contributes to the discussion about the role of cluster organisations and their economic impact.